2020
DOI: 10.1101/2020.12.02.20242370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of human genetic variation on Epstein-Barr virus sequence diversity

Abstract: Epstein-Barr virus (EBV) is one of the most common viruses latently infecting humans. Little is known about the impact of human genetic variation on the large inter-individual differences observed in response to EBV infection. To search for a potential imprint of host genomic variation on the EBV sequence, we jointly analyzed paired viral and human genomic data from 268 HIV-coinfected individuals with CD4+ T cell count <200/mm3 and elevated EBV viremia. We hypothesized that the reactivated virus circulating… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Associations between host variants and specific pathogen genetic loci are not unique to TB, and have recently been found in many other infectious diseases such as human immunodeficiency virus, hepatitis C virus, Epstein-Barr virus and Streptococcus pneumoniae bacteria( 3437 ). Our study argues that inclusion of the genetic sequences of infectious agents can offer novel biological insights to future genetic studies of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between host variants and specific pathogen genetic loci are not unique to TB, and have recently been found in many other infectious diseases such as human immunodeficiency virus, hepatitis C virus, Epstein-Barr virus and Streptococcus pneumoniae bacteria( 3437 ). Our study argues that inclusion of the genetic sequences of infectious agents can offer novel biological insights to future genetic studies of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between host variants and speci c pathogen genetic loci are not unique to TB, and have recently been found in many other infectious diseases such as human immunode ciency virus, hepatitis C virus, Epstein-Barr virus and Streptococcus pneumoniae bacteria [35][36][37][38] . Our study argues that inclusion of the genetic sequences of infectious agents can offer novel biological insights to future genetic studies of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the majority of studies on EBV genotyping were limited to certain regions. Moreover, it was reported that EBV sequence variation is associated with host sequence variants, hence, joint analyses of host and viral genome variation would help decipher the pathogenesis of NPC and identify novel diagnostic and therapeutic targets (Rüeger et al, 2021). Studies recruiting larger samples involving individuals with different conditions from different ethnic groups and geographical regions are needed to determine the exact association of EBV strains with the geographical distribution and development of the disease.…”
Section: Ebv Subtypesmentioning
confidence: 99%